Investigation of the relationship between lymphocyte subsets and intestinal parasites - Mulayim, Sefa; Dalkilic, Semih; Akbulut, H. Handan; Aksoy, Asude; Kaplan, Mustafa (Elsevier, 2022)
We analyzed the peripheral blood lymphocyte subsets of cancer patients infected with intestinal parasites, with an aim to find out the relationship between the levels of different types of lymphocytes with the prognosis of patients. 201 cancer patients aged 18 and over were included. Stool samples of the patients were examined using native-lugol, trichrome, modified trichrome (Weber's Trichrome stain), and modified Ziehl-Neelsen staining methods. Microsporidia and Cryptosporidium parvum were investigated at the genus and species levels using PCR. Lymphocyte subsets were determined by flow cytometry in blood samples. One or more parasite species were detected in 115 (56.7%) patients. The most common parasite species were Microsporidia, Blastocystis and Entamoeba coli, respectively. The frequency of parasites was high in patients with low lymphocyte percentage, CD3(+) T cell and CD3(+) CD4(+) T (Th) cell levels in blood samples studied by flow cytometry. Microsporidia infection was significantly higher in patients with low lymphocyte percentage and Th cell levels. Similarly, C. parvum infection was found to be significantly higher in patients with low T lymphocyte percentage and Th cell level. Finally, Blastocystis infection was significantly higher in patients with low lymphocyte percentage and CD4/CD8 ratio higher than 1. The decrease in lymphocyte percentage, CD3(+) T cell and Th cell count, and low CD4/CD8 ratio in cancer patients increase the frequency of intestinal parasitic infections. Based on these results, lymphocyte subsets may help identify cancer patients at high risk of opportunistic parasites. We suggest that opportunistic parasitic infections affecting the clinical course of the disease should be considered by clinicians during the follow-up and treatment of patients.
Keywords: Intestinal parasites; Lymphocyte subsets; Cancer patients